TINGKAT KEPATUHAN TENAGA KERJA KONSTRUKSI DALAM IMPLEMENTASI PELAKSANAAN K3 PADA PROYEK KONSTRUKSI DI KOTA SURAKARTA - Susila, Herman; Joko Priyanto, Kusdiman; Agtya Putra, Yusuf; Setyo Hidayat, Wisnu (Jurnal Teknik Sipil dan Arsitektur, 2026)
Surakarta (Solo), as one of the major cities in Central Java, is experiencing rapid development in the construction sector, both for commercial, residential, and infrastructure projects. The implementation of SMKK (Vocational Occupational Safety and Health) in construction projects in Surakarta is certainly a very important aspect to create a safe, healthy work environment, and avoid potential work accidents. Occupational Safety and Health (K3) is an important aspect in construction projects to prevent work accidents and increase worker productivity. However, the level of compliance with K3 in the field remains a significant challenge. This study aims to analyze the level of worker compliance with K3 in construction projects and the factors that influence it. The research method uses a quantitative approach by distributing questionnaires to construction workers and field observations. Testing in this study uses descriptive statistical methods. This study shows that worker compliance with K3 in Surakarta City is in the good category with an average of 3.078. The Top Management Commitment to K3 variable has the highest compliance level (3.13), while the K3 Regulations and Procedures variable has the lowest compliance value (3.01). For other variables are the Use of PPE (3.113), Worker Communication (3.093), Work Environment (3.09), Worker Competence (3.027). From these results, to increase the level of compliance of construction workers in implementing K3, further efforts are needed in the form of increased education and stricter supervision.